2019
DOI: 10.1017/s0376892919000055
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitivity Analysis of the Application of Integrated Species Distribution Models to Mobile Species: A Case Study with the Endangered Baird’s Tapir

Abstract: SummarySpecies distribution models (SDMs) are statistical tools used to develop continuous predictions of species occurrence. ‘Integrated SDMs’ (ISDMs) are an elaboration of this approach with potential advantages that allow for the dual use of opportunistically collected presence-only data and site-occupancy data from planned surveys. These models also account for survey bias and imperfect detection through the use of a hierarchical modelling framework that separately estimates the species–environment respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The prediction of the distributions of species is central to diverse applications in ecology, evolution, and conservation science (Elith et al, 2006). In particular, with species facing a high degree of global threat, distribution modelling may allow effective conservation strategies to be undertaken (Maiorano et al, 2019; Schank et al, 2019). The relatively long‐term dataset analysed (including 10 years from a period of 13 years) accounts for some interannual variability (Tummon et al, 2015), whereas previous studies of the distribution of this species covered more limited time periods (Arcos et al, 2009; Louzao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of the distributions of species is central to diverse applications in ecology, evolution, and conservation science (Elith et al, 2006). In particular, with species facing a high degree of global threat, distribution modelling may allow effective conservation strategies to be undertaken (Maiorano et al, 2019; Schank et al, 2019). The relatively long‐term dataset analysed (including 10 years from a period of 13 years) accounts for some interannual variability (Tummon et al, 2015), whereas previous studies of the distribution of this species covered more limited time periods (Arcos et al, 2009; Louzao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the resolution of the analysis can have significant effects on the results, for both the ISDM and the connectivity (i.e. least-cost) analysis (Etherington, 2016;Schank et al, 2019). We selected a resolution we deemed appropriate for the ISDM, but future research would benefit from further evaluating this choice for the leastcost path analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The ISDM was fit using custom R code adapted from previous research (Dorazio, 2014;Schank et al, 2017Schank et al, , 2019.…”
Section: Poisson Point Process -Used Across a Variety Of Applications (From Astronomy Tomentioning
confidence: 99%
“…For example, Fernandes et al (2018) showed that models with high fit (e.g., using Random Forest) were more negatively influenced by errors and biases (lower predictive success) compared with models with lower fit (e.g., GLMs), whereas models assuming a linear relationship (e.g., GLMs/GLMMs) are more affected by collinearity and multicollinearity. Schank et al (2019) showed that integrated distribution models can improve the handling of sampling bias whereas Tobler et al (2019) discuss the impact of measurement errors and correlation between objects in joint distribution models.…”
Section: Step 3: Modeling Method: Choice Tuning and Parameterizationmentioning
confidence: 99%